Identifying the substitution effect of temporary agency employment - Elke J. Jahn; Enzo Weber (Institute for the Study of Labor (IZA), 2012)
This paper fills a gap in the literature by investigating whether temporary agency employment substitutes regular employment. To take into account the interaction between the two employment forms, we identify a SVAR model with correlated innovations by volatility regimes. We show that a positive shock to temporary agency employment increases overall employment, but also leads to substitution of regular jobs.
urn:nbn:de:101:1-2012080812085
Keywords: C32; J21; J41; 330; temporary agency employment; substitution effect; Germany; Leiharbeit; Beschäftigungseffekt; Arbeitsverhältnis; Substitutionseffekt; Schätzung; Deutschland